1975
DOI: 10.21273/jashs.100.2.129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mechanical Harvesting on Yield, Quality of Fruit and Bush Damage of Highbush Blueberry1

Abstract: On 15 occasions, either Wolcott, Jersey, Morrow or Murphy cultivars of highbush blueberry (Vaccinium corymbosum L.) were harvested by commercial hand-pickers and over-the-row mechanical harvesters in eastern NC during 1970 and 1971. Compared with hand-harvesting, machine-harvesting reduced yield of marketable ripe fruit 19 to 44%. Compared with commercially hand-harvested fruit, machine-harvested fruit was 10 to 30% softer in compression tests; and when held for 7 days at 21°C, the fruit developed 11 to 41% mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…Total cullage after mechanical harvest averaged 31%. This is similar to values reported by Mainland et al (7) for highbush blueberries. Our data do not include ripe, overripe, or green fruit lost on the ground from mechanical harvest.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Total cullage after mechanical harvest averaged 31%. This is similar to values reported by Mainland et al (7) for highbush blueberries. Our data do not include ripe, overripe, or green fruit lost on the ground from mechanical harvest.…”
Section: Resultssupporting
confidence: 93%
“…Our data do not include ripe, overripe, or green fruit lost on the ground from mechanical harvest. For mechanically harvested fruit, ground losses ranged from 8 % on young, well-pruned plants (1) to 29% on mature plants (7). For commercially hand-harvested fruit, ground loss ranged from 2 % to 8 % (1, 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports (1,3,20,22) have shown that mechanical harvest reduces fruit firmness and storage life when blueberries are stored in air. In this study, quality, as indicated by marketable fruit, firm fruit, and sensory ratings of either hand-or machine-harvested rabbiteye blueberries stored in atmospheres containing 15% or 20% C 02 and 5% 0 2 were substantially better than quality of blueberries stored in air.…”
Section: Resultsmentioning
confidence: 99%
“…Blueberries were less firm and exhibited more postharvest decay when harvested by machine than when harvested by hand (1,3,20,22). The stem scar has been identified as the primary Received for publication 22 June 1987.…”
mentioning
confidence: 99%